1,4,5,8-tetrasubstituted dihydroanthracene-based triptycene trisquinones: Synthesis, structural, and physicochemical characterization - Hyun, Chang-Seok; Eo, Joohwan; Kwon, Ji Eon; An, Byeong-Kwan (Marcel Dekker Inc., 2024)
1,4,5,8-tetrasubstituted dihyroanthracene-based triptycene trisquinones (TT) molecules, THAO-TT and tris(THAO)-TT, were synthesized by Diels-Alder reaction between TT and 1,4,5,8-tetrakis(hexyloxy)anthracene to produce the extended triptycene derivatives containing electron-accepting functionality. The prepared THOA-TT and tris(THOA)-TT exhibited excellent thermal stability owing to the rigid TT framework. The optical and redox properties of THOA-TT and tris(THOA)-TT were controlled by the homoconjugation between the benzoquinone units and the peripheral units through the connecting methine groups.